PERANCANGAN KURSI TERAS DENGAN MEMADUKAN MATERIAL BESI PIPA DAN KAYU DENGAN EVALUASI ERGONOMI - Pertiwi, Ratih; Karsono, Ibnu Dwi (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2018)
The design of the product seats are often found and traded more focused on functional aspects and less see the product keergonomisan. UD.Sumber Rejeki is an industry engaged in wood working & furniture. With ergonomics is expected to analyze the design of the old chair, then proposed the design of a chair that is more ergonomic. In this study, we analyzed how to design a terrace chair that takes into account the ergonomic factors that are adjusted to the average physical condition of Indonesian core chairs users.